The United States and the Treaty Law of the Sea - Reiff, Henry, 1899- (Book collections on Project MUSE., 1959)
This volume makes available, for the first time, a systematic and analytical account of an important aspect of America's relation to the sea and to the other nations using the sea. Professor Reiff traces the record of the United States' participation in treaties which seek to regulate the peacetime use of the sea, its resources, and the air space over it. The emphasis is upon contemporary developments but the study covers the entire period of the Republic. A brief summary of the physical facts about the sea provides a realistic frame of reference for the discussion of international problems and their solutions. Professor Reiff describes current uses and abuses of the sea with respect to transportation, communications, exploitation of products and energy, disposal of waste, and recreation. Throughout the book, he relates developments in economics, technology, social science, and the natural sciences to the expanding web of treaty law. Among the important topics covered are atomic and oil pollution of the sea, nuclear weapons and guided missiles testing at sea, the International Geophysical Year and its predecessors, the First and Second Polar Years, sea traffic in narcotics and slaves, and the St. Lawrence Seaway. The results of the United Nations Conference on the Law of the Sea, held in 1958, are summarized, and the report of the United Nations International Law Commission which led up to the conference is analyzed in detail. Government and shipping officials, naval and marine personnel, and specialists in maritime and international law will find this a useful and significant book.